GEOLOGICAL, PETROLOGICAL AND TECTONIC FEATURES CHARACTERIZING THE COMMERCIALITY OF THE MARBLES OF SOUTHERN VERMION MOUNTAIN - Ploumis, P.; Chatzipanagis, I. (Bulletin of the Geological Society of Greece, 2010)
The southern Vermion mountain is composed of Pelagonian metamorphic rocks. Two different lithologic units are distinguished in this area. The first one consists of the highly metamorphosed rocks of Paleozoic age (migmatites, gneisses with marble intercalations and anatectic granites). The second unit comprises two series: the lower with schists, gneisses and marbles (200 m thick) and the upper with marbles (more than 2500m thick). The age of the rocks in the second unit is Triassic –Jurassic and these are metamorphosed in greenshist facies. During the last 40 years, the marbles of the second unit are being exploited for ornamental purposes in more than 100 quarries.Variations in chemical and mineralogical composition, grain size as well as some structural characteristics result to the 5 marble qualities – commercial types of Vermion mountain: a) White marbles, b) “Rigota” marbles, c) “Pitsilota” marbles, d) “Louloudata” marbles, e) Sipoline marbles.